Stratejik bilincin karar verme stilleri üzerindeki etkisinde risk alma algısı ve çevresel belirsizliğin rolü - Çakarel, Taha Yusuf (My University, 2023)
Start-Up ekosistemi dünyada olduğu gibi ülkemizde de çok hızlı büyümekte, bu alana olan ilgi gün geçtikçe artmaktadır. Rekabetin çok yoğun olduğu bu ekosistem içerisinde sürdürülebilir rekabet üstünlüğü elde etmek oldukça önemli bir hal almaktadır. Girişimcinin stratejik bilince sahip olması, faaliyetlerini ve kararlarını bu perspektif dahilinde vermesi oldukça önemlidir. Girişimci için kritik faktörlerden biri de karar verme sürecinin belirleyicilerinden biri olan karar verme stilleri olarak ifade edilmektedir. Girişimci her ne kadar risk alan birey olarak tanımlansa da riski nasıl algıladığı ve riske karşı nasıl bir tutum sergilediği de oldukça önemlidir. Teknolojinin hızlı gelişimiyle birlikte yaşanan dijitalleşme sürecinde, her sektörde, her işletme için olduğu gibi start-up ekosistemi için de belirsizlik durumları söz konusu olmaktadır. Bu çalışmada, ülkemizde bir teknopark ya da teknokentte veya teknoloji transfer ofisi ya da merkezinde kurulan ve faaliyetlerini sürdüren start-up girişimcilerinin stratejik bilinç düzeylerinin karar verme stilleri üzerindeki etkisi incelenmiş olup, yine bu start-up girişimcilerinin risk alma algısı ve çevresel belirsizliğin bu ilişki üzerindeki rolü araştırılmıştır. 19 start-up girişimcisiyle yarı yapılandırılmış mülakatlar çerçevesinde elde edilen bulgular kapsamında, start-up girişimcilerinin stratejik bilinç düzeylerinin karar verme stilleri üzerinde anlamlı bir etkisinin olduğu, bu ilişkide de risk alma algılarının ve çevresel belirsizliğin ayrı ayrı rolleri olduğu tespit edilmiştir.

The Start-Up ecosystem is growing very fast in Turkey as well as in the world, and interest in this field is increasing day by day. In this highly competitive ecosystem, achieving sustainable competitive advantage becomes paramount. It is crucial for entrepreneurs to possess strategic consciousness and base their activities and decisions within this perspective. One of the critical factors for entrepreneurs is expressed as decision-making styles, which is one of the determinants of the decision-making process. Although entrepreneurs are commonly defined as risk-taking individuals, how they perceive risk and what kind of attitude they exhibit towards risk are also equally significant. Through the ongoing digitalization process driven by the rapid advancement of technology, uncertainty permeates the start-up ecosystem, much like it does in every sector and business. This study examines the impact of strategic consciousness levels on the decision-making styles of start-up entrepreneurs who are established and operate within a science park or technology transfer office in Turkey. Additionally, it delves into the risk-taking perceptions of these start-up entrepreneurs and studies the impact of environmental uncertainty on this relationship. Based on findings derived from the semi-structured interviews conducted with 19 start-up entrepreneurs, it was established that the strategic consciousness levels of entrepreneurs significantly affect their decision-making styles. Furthermore, it was observed that risk-taking perceptions and environmental uncertainty play distinct roles in shaping this relationship.
The role of Risk taking and environmental uncertainty in the impact of strategi̇c consciousness on decision making styles
Keywords: Çevresel Belirsizlik; Decision making; Decision Making Styles; Environmental Uncertainty; Karar verme; Karar Verme Stilleri; Risk Alma; Risk Taking; Start-Up; Start-Up Strategic Consciousness; Stratejik Bilinç